The Qur’anic Reflection on Hedonism: Contemplative Study of the Stories of Saba’ and Qarun in the Qur’an - Fikri Alfani Hakim (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
Background and Objectives: The phenomenon of modern hedonism is increasingly widespread, characterized by consumerist culture, displays of wealth, and the pursuit of material possessions as the ultimate source of happiness. The Qur’an firmly criticizes such a lifestyle through the stories of past nations that faced destruction due to their neglect of spiritual values. Therefore, this study aims to reflect on hedonistic behavior through the stories of Qarun and the people of Saba’, as presented in Q.S. al-Qasas: 76–81 and Q.S. Saba’: 15–16. Method: This research employs a qualitative method based on library research with a tafsir tahlili approach, analyzing the verses systematically and in depth by referring to contemporary tafsir works. Main Results: The study reveals that the story of Qarun illustrates arrogance and denial of God’s blessings, accompanied by a low level of spiritual awareness. The people of Saba’ represent a prosperous society that failed to show gratitude, ultimately leading to their downfall. Contributions: This research contributes by linking the two Qur’anic stories with modern social realities concerning human psychological conditions and offers Qur’anic solutions to confront consumerist and materialistic lifestyles. Conclusions: The stories of Qarun and the people of Saba’ in the Qur’an serve as moral lessons that remain highly relevant to today’s realities, such as the hedonistic phenomena of